Identification and Monitoring of Dominant Patterns of Food, Sleep and Physical Activity and Related Factors in Fasa in Year 2017: An Exploratory Factor Analysis - pezhman bagheri; Mouhebat vali; zahra maleki (Journal of Advanced Biomedical Sciences, 2020)
Background & Objectives: The analysis of sleep patterns, food and physical activity provides researchers with a focus on chronic disease prevention. The aim of this study was to determine the dominant patterns of food, sleep and physical activity and related factors in Fasa in 2017. Materials & Methods: In this cross-sectional study, 500 adults in Fasa were collected by multi-stage cluster sampling using a combination of Pittsburgh Sleep Quality Questionnaire, food Frequency and International Physical Activity Questionnaire. Factor analysis was used to identify the dominant patterns and in order to determine the relationship between variables, linear regression test was used. Results: The mean age of the participants was 35.02 ± 12.68 years. The three dominant food patterns were healthy (24.35%), unhealthy (18.31%) and miscellaneous (12.98%), sleep disorders including primary sleep disorder (17.90%), secondary (16.60%) and third (12.46%) and physical activity also included light physical activity (37.09%), moderate (5.86%) and severe (16.26%). Also, variables such as age, gender and socioeconomic status were introduced as the main predictors of patterns. Conclusion: Considering the high share of unhealthy patterns in the population of the city as an example of the urban population of southern Iran, the need for planning and raising awareness and education in order to increase physical activity and improve sleep and nutrition, as well as improve the quality of life and general health of individuals in society is increasingly felt.